2021
DOI: 10.1016/j.arrct.2021.100105
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Reported Pain Management Practices for Individuals With Cerebral Palsy

Abstract: Objective To investigate types and intensity of pain experienced by individuals with cerebral palsy (CP) and common pain-relieving approaches used by caregivers. Design The approach was cross-sectional, using standardized interviews. Setting Individuals with CP were recruited from a specialty health care hospital. Participants Eighty-six individuals (N=86; mean age, 17.2 years; male, 58%) with CP and complex commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This may be explained by the fact that older caretakers have much more experience of recognition of pain, and may be giving more support to relieve this chronic pain. In a study done by Abigail M et al in 2021, it showed that caretakers were able to report different types of pain but also used non pharmacologic approaches such as changing positions, massage as well as medication to relieve pain in children with CP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that older caretakers have much more experience of recognition of pain, and may be giving more support to relieve this chronic pain. In a study done by Abigail M et al in 2021, it showed that caretakers were able to report different types of pain but also used non pharmacologic approaches such as changing positions, massage as well as medication to relieve pain in children with CP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We are encouraged by recent work; for example, a pain assessment toolbox and clinical practice points specific to pain in children with physical disabilities were developed and disseminated, 11,12 pain education programs have been developed for caregivers and tested for effectiveness, [13][14][15] and while still severely limited, studies are starting to emerge focused on understanding pain management approaches in this population. [16][17][18][19][20] This special issue features important and diverse research spanning pain prevalence, assessment, and management in children with IDD. We are also pleased to highlight a knowledge mobilization project focused on impacting care and the human experience.…”
mentioning
confidence: 99%
“…We are encouraged by recent work; for example, a pain assessment toolbox and clinical practice points specific to pain in children with physical disabilities were developed and disseminated, 11 , 12 pain education programs have been developed for caregivers and tested for effectiveness, 13 , 14 , 15 and while still severely limited, studies are starting to emerge focused on understanding pain management approaches in this population. 16 , 17 , 18 , 19 , 20 …”
mentioning
confidence: 99%